Understanding factors influencing traveler’s adoption of travel influencer advertising: an Information Adoption Model approach - Nadlifatin, Reny; Persada, Satria Fadil; Munthe, Josua Hasiholan; Ardiansyahmiraja, Bobby; Redi, Anak Agung Ngurah Perwira; Prasetyo, Yogi Tri; Belgiawan, Prawira Fajarindra (Business: Theory and Practice, 2022)
In the service sector, such as tourism and hospitality, a traveler often tries to find information about their destination digitally, comparing it to alternatives available to have the best option. This demand businesses that are in the tourism and hospitality sector to advertise their destination more creatively and informatively, such as using a travel influencer. The present research was conducted to explore how the public adopts information advertised by a social media influencer that promotes travel or leisure places, better known as a travel influencer. The Information Adoption Model (IAM) was used to explore the factors that could affect people’s perception of Information Usefulness (IU), which then affects Information Adoption (IA). Several hypotheses that were built from the IAM theoretical framework were tested using Partial Least Square Structural Equation Modelling (PLS-SEM) with 150 people as respondents; four out of the seven hypotheses were accepted. From the accepted hypotheses, it was revealed that more dimensions in the Source Credibility construct influence Information Usefulness compared to the dimensions from the Argument Quality constructs.